200k views
3 votes
PleaseeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeSimplify -2^3

User Boris K
by
5.2k points

1 Answer

4 votes

Answer:

Therefore,


(-2)^(3)=-8

Explanation:

Simplify

-2^3


(-2)^(3)

It is read as negative 2 raised to the power three,

also it is the cube of negative 2

we know that
a^(3)given as


a^(3)=a* a* a

so for negative a i.e -a


(-a)^(3)=-a* -a* -a

substituting a = 2 we get


(-2)^(3)=-2* -2* -2

negative sign multiplied by odd number of times then the sign remains negative.

Therefore,


(-2)^(3)=-8

User Crymson
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.